An investigation of the reliability analysis of speaking test - Khan, Raja Muhammad Ishtiaq; Noor Raha, Mohd Radzuan; Shahbaz, Muhammad; Kumar, Tribhuwan (English Language Education Publishing, 2020)
Speaking skill is marked as one of the most significant for language learning. The assessment of the oral test remained difficult because of the involvement of humans. The speaking assessment is based on the reliability of the test and reliability relies on the raters' score. To this, the present study is an attempt to estimate the inter-rater reliability of the Speaking test used in the Common First Year program (CFY) of a public university in Saudi Arabia. The data were collected through a scoring sheet from 62 EFL learners. 6 raters were involved in the rating of 61 participants of the study. Quantitative data analysis was used to estimate the reliability of the speaking test. The correlation coefficient and Bland-Altman test were used to measure the agreement between the raters. SPSS was used for data analysis in the present study. The result of the study indicated that the speaking test used in the CFY program is in the accepted norm of the reliability values.